Anquilosis dentaria - Zapata-N., Oscar A.; Giraldo-F., Monica P. (Revista Facultad de Odontología Universidad de Antioquia, 2016)
A brief description is done, because it’s the purpose of this bibliographic review about ankylosis. This exposes too differents theories to this day, about etiology, and gives some clinic and radiografic elements to get a good diagnostic and to see the effects on the oclussion development.